2012
DOI: 10.1002/ece3.263
|View full text |Cite
|
Sign up to set email alerts
|

Climatic niche shift predicts thermal trait response in one but not both introductions of the Puerto Rican lizard Anolis cristatellus to Miami, Florida, USA

Abstract: Global change is predicted to alter environmental conditions for populations in numerous ways; for example, invasive species often experience substantial shifts in climatic conditions during introduction from their native to non-native ranges. Whether these shifts elicit a phenotypic response, and how adaptation and phenotypic plasticity contribute to phenotypic change, are key issues for understanding biological invasions and how populations may respond to local climate change. We combined modeling, field dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 65 publications
4
60
0
Order By: Relevance
“…Thus, the results are consistent with recent evidence that geographical clines in introduced insects and plants can evolve within tens of generations (e.g. [42,43]), and with studies of vertebrates that have demonstrated adaptive divergence across a similar number of generations [2,3,5,[44][45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the results are consistent with recent evidence that geographical clines in introduced insects and plants can evolve within tens of generations (e.g. [42,43]), and with studies of vertebrates that have demonstrated adaptive divergence across a similar number of generations [2,3,5,[44][45][46][47].…”
Section: Discussionsupporting
confidence: 91%
“…armouri (Loma de Toro, elevation ÂŒ 2318 m; n ÂŒ 18) and A. cybotes (Los Patos, elevation ÂŒ 45 m; n ÂŒ 19). Kolbe et al [44] found that a two-week acclimatization at 22.58C was sufficient to elicit a strong plastic response in CT min in a lowland population of Anolis cristatellus from Puerto Rico without inducing severe thermal stress. We maintained lizards at 19.48C (range ÂŒ 17.48C-21.98C) for three weeks and measured CT min following the procedure described above.…”
Section: (D) Cold-acclimatization Trialsmentioning
confidence: 99%
“…Hypotheses explaining introduction outcomes can be classed as those considering factors to do with the introduction event, the location of introduction, or the characteristics of the species (Liu et al 2014). Contingency plays a role in many hypotheses: for example, trait variation in the founding populations (not all variation in the original population is present in the introduced population) ( Kolbe et al 2012), propagule pressure (the number of individuals released in the introduced area) ( Colautti et al 2006), admixture (individuals from different parts of the native range that normally do not mix) (Kolbe et al 2007) and secondary releases (increases net propagule pressure, and may result in admixture) (Kowarik 2003). The location of the introduction is important.…”
Section: Introductionmentioning
confidence: 99%